Psychomotor Abilities, Body Composition and Training Experience of Elite and Sub-Elite Handball Players - Maciej Śliż; Cintia França; Francisco Martins; Patryk Marszałek; Élvio Rúbio Gouveia; Krzysztof Przednowek (Applied Sciences)
Background: Handball is characterized by fast and dynamic movements requiring appropriate psychomotor abilities and body mass composition. High levels of reaction and movement time can be crucial factors influencing quick reactions and in-time decision-making at the handball court. The aim of this study was to assess psychomotor abilities among elite and sub-elite Polish and Portuguese male and female handball players at the different levels of competition. Methods: Computer Test2Drive systems were used to assess reaction time, movement time and percentage of correct responses of 199 handball players (60 females). Results: Statistically significant correlation was noted between SIRT cr and the Elite group (r = 0.44) and between the CHORT cr and all groups (r = 0.33). A statistical correlation between CHORT MT and total body water (r = 0.44) was also noted in Elite handball players. Conclusions: High level of psychomotor abilities and body composition seems to have impact on the competitive level in male and female handball players.